From a Reckoning to Racial Concordance: A Strategy to Protect Black Mothers, Children, and Infants - Johnson, Nia (The Hastings Center report, 2022)
The grave state of health among Black Americans warrants reexamination of how to mitigate health disparities. In this commentary, which responds to the important concerns Nneka Sederstrom and Tamika Lasege raise in "Anti-Black Racism as a Chronic Condition," I argue that the use of racial concordance for Black patients can be a step toward reducing mortality rates and health care negligence for Black people. Racial concordance involves aligning patients with providers of their same race to mitigate implicit bias. Racial concordance is imperfect, but the unjust rates of mortality and other adverse health outcomes that Black Americans face each day in health care facilities may warrant taking seriously this solution.